DERITA KONFLIK DALAM HARIAN AMBON EKSPRES Study Tanggung Jawab Media dalam Menciptakan Stabilitas Sosial Politik di Maluku - Arifuddin Arifuddin; Telly Muriany (Jurnal Masyarakat Telematika dan Informasi, 2010)
The aim of this research is to know the factuality, the impartiality and the social impact of Harian Ambon Ekspres in reporting conflict in Maluku. This is a qualitative descriptive research that using a content analysis method in analyzing the whole conflict report content in Harian Ambon Ekspres in order to elaborate the journalistic rule that applied by Harian Ambon Ekspres institution relating to the social and politic stability in Ambon. The analysis units in this research are the conflict report that served in Harian Ambon Ekspres in early 2008 until February 2009 period with types of SARA (clan, religion, race and groups), socio-cultural and politic Conflict Report. The result of the research indicate that, according to the factuality most of the report that served suitable to the facts that happen, this is because of the existence of the official confirmation source from the in service government and security apparatus at the conflict area. Otherwise, according to the impartiality, the unbalance report service is dominant in Harian Ambon Ekspres journalistic practice, this is because of the un-existence of certain party confirmation as the conflict contestant and the cover both sides practice. Factual information presentation without journalistic ethic limitation and partial report presentation has a negative impact and it is nonsupport in creating social and politic stability in the community around the conflict area.